ANALISIS IMPLEMENTASI KEBIJAKAN PELATIHAN POLA SATU PINTU DENGAN MODEL EDWARD III DI KABUPATEN GORONTALO - ENDI TRIYANTO MANYO’E (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
The purpose of writing the article is to determine the effectiveness of the one-stop integrated training policy from the perspective of policy formulation. The writing in this article uses a qualitative approach with the category of library research. This research stage begins with determining the research topic, followed by reviewing the latest literature, reducing literature, organizing literature, reviewing literature and drawing conclusions. The results of the study indicate that the implementation of the one-door pattern training policy in Gorontalo Regency has not been effective in its implementation, especially in the aspects of communication, resources (training and training facilities) and disposition (commitment of partner regional apparatus). Meanwhile, for the aspect of bureaucratic structure, it has shown good performance. To further optimize the one-door pattern training policy, it is necessary to improve the existing regulations into Regional Regulations so that these policies have more